Evidence and projections on the progressivity of health care financing in Finland - Jan Klavus; Pekka Rissanen (University of Oslo, 2018)
This paper examined the distribution of health care financing in Finland in 1990-2012. In addition, the study provided insight to recent developments in the financing system, and analyzed various scenarios associated with the planned financing reform of 2020. The results indicated, that over the two decade study period overall progressivity first steadily decreased, and after turning regressive by 2006, returned to a progressive track leading to the highest level of measured progressivity by 2012. The distributional implications of the financing reform in the "stationary" scenario were shown to be significant; substituting revenue collected previously by local income taxes by an equiproportinate increase in state income tax revenue would increase the progressivity of overall financing to an unprecedentedly high level. In the "counterbalanced" scenario, where the state income tax scales were adjusted to correspond to the average income tax rate, the progressivity of overall financing increased more moderately. Finally, the "system-level" scenario indicated that taking into account recent changes in other financing sources outweighed the progressivity effect, and a slightly less progressive overall financing distribution would emerge in 2020 in comparison to 2012. The monetary effects of abolishing the public reimbursement scheme of private health services fees were shown to be rather small in magnitude, but the economic burden fell more heavily on low-income households.   Published: Online May 2018.